Mitigating salt stress in saline-alkali soils through co-application of superabsorbent carbon-based material and flue gas desulfurization gypsum - Zhang, Shengnan; Yang, Youming; Zhang, Juanxiang; Qian, Xiaoyan (Frontiers in Soil Science, 2025)
Flue gas desulfurization gypsum (FGD) and biochar are considered effective amendments for alleviating soil salinity stress. However, the co-application of these amendments in practice requires further investigation. This study successfully prepared a superabsorbent carbon-based material (CB) via graft polymerization and applied it in combination with FGD to investigate their effects on leaching salt ions and improving saline-alkali soil. A laboratory soil column leaching experiment was conducted with six treatments: control (CK, no amendment), cotton straw biochar (BC), CB, FGD, BC+FGD, and CB+FGD. Field plot trials were further employed to evaluate the soil amendment efficacy. The results demonstrated that the co-application of the CB and FGD significantly alleviated salt stress by promoting Na+ leaching. During the P1 (sharp decrease) leaching phase, Na+ leaching concentrations under the sole FGD and CB+FGD treatments increased by 89.08% and 90.92%, respectively, compared to CK. Co-application with FGD significantly increased the content of Ca2+ and SO42- in the soil. The CB effectively retained soil K+, and the Cl- content after leaching was significantly lower than in CK. Field trials further confirmed that the co-application of the CB and FGD significantly reduced the contents of Na+, Cl-, and Mg2+ while increasing the contents of Ca2+, K+, and SO42-. The contents of Na+, Cl-, and K+ increased with soil depth, indicating the migration of major salt ions towards deeper soil layers with water movement. The CB+FGD treatment significantly reduced soil TSS, electrical conductivity (EC), and SAR. In conclusion, the co-application between the CB and FGD enhances salt leaching efficiency and soil water retention capacity, exerting a positive influence on the remediation of saline-alkali soils. This study provides a novel strategy for utilizing agricultural waste in saline soil management.